Anticholinergic Drugs in Nonallergic Rhinitis - Robert Naclerio, MD (World Allergy Organization Journal, 2009)
Background: The parasympathetic nervous system contributes to the pathophysiology of multiple forms of allergic and nonallergic rhinitis. Stimulation of the parasympathetic nervous system leads to glandular activation, which produces watery secretions. In excess, these secretions discharge from the anterior Nares and produce the symptom of watery anterior rhinorrhea.Method: Review of literature.Results: Treatment with topical, intranasal anticholinergic drugs inhibits activation of the nasal mucosal glands and is effective in reducing the watery secretions associated with parasympathetic stimulation of the glands with little, if any, effect on the symptoms of congestion and sneezing. In general, these drugs have no systemic adverse effects, but can cause crusting and local irritation.Conclusion: Anticholinergic drugs are useful for the treatment of anterior rhinorrhea associated with allergic and nonallergic rhinitis. Keywords: anticholinergic, atropine, ipratropium bromide, rhinitis, nonallergic rhinitis